A narrative review of the epidemiology, diagnosis, and treatment of latent stress urinary incontinence. (7th May 2019) - Edenfield, Autumn; Patnam, Radhika; Swift, Steven
Abstract : Aims: To review the current literature on the development of latent stress urinary incontinence (SUI) or SUI that occurs following pelvic organ prolapse therapy in patients who were continent prior to therapy. To make recommendations on how to best evaluate and manage patients with pelvic organ prolapse who are continent. Methods: This is a narrative review using Google scholar and cross referencing identified manuscripts. We used the British Medical Journals grading of literature to assign letter grades to level of statements and recommendations. Results: The literature suggest about 40% of women with advanced pelvic organ prolapse who are continent will develop SUI after surgery to correct their pelvic organ prolapse. Reduction cough stress testing can help identify those patients at risk to develop SUI with a PPV of 60%. Reduction cough stress testing is best done using large rectal swabs or scopettes. The literature on how to best manage patients with advanced pelvic organ prolapse and are continent to avoid latent SUI is mixed and the best recommendations are based on sound literature that is incomplete. Conclusions: Understanding that latent SUI is a potential complication in any subject with advanced pelvic organ prolapse is necessary to pre‐operative counseling. Deciding on the best management strategy is not clear cut and therefore should involve patient input in the decision making process.